2017
DOI: 10.1007/s13311-016-0492-9
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Excitability in Amyotrophic Lateral Sclerosis

Abstract: Axonal excitability testing provides in vivo assessment of axonal ion channel function and membrane potential. Excitability techniques have provided insights into the pathophysiological mechanisms underlying the development of neurodegeneration and clinical features of amyotrophic lateral sclerosis (ALS) and related neuromuscular disorders. Specifically, abnormalities of Na and K conductances contribute to development of membrane hyperexcitability in ALS, thereby leading to symptom generation of muscle cramps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 147 publications
0
35
0
Order By: Relevance
“…In ALS, it showed evidence of increased persistent sodium-conductance and reduced potassium-conductance, both of which may contribute to axonal hyperexcitability and fasciculation. [2][3][4][5][6] Furthermore, the presence of increased persistent sodium-conductance was shown to be correlated with more rapid functional decline and shorter survival, 7,8 and the presence of fasciculation with shorter survival. 9 Because increased membrane excitability in ALS may be a relevant step in the cascade leading to structural damage of motor neurons, 10 early identification of hyperexcitable motor neurons may provide an argument for initiating neuroprotective intervention.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
See 1 more Smart Citation
“…In ALS, it showed evidence of increased persistent sodium-conductance and reduced potassium-conductance, both of which may contribute to axonal hyperexcitability and fasciculation. [2][3][4][5][6] Furthermore, the presence of increased persistent sodium-conductance was shown to be correlated with more rapid functional decline and shorter survival, 7,8 and the presence of fasciculation with shorter survival. 9 Because increased membrane excitability in ALS may be a relevant step in the cascade leading to structural damage of motor neurons, 10 early identification of hyperexcitable motor neurons may provide an argument for initiating neuroprotective intervention.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
“…Excitability testing is a neurophysiological tool that allows noninvasive assessment of axolemmal voltage‐gated ion‐channel activity in motor axons of a peripheral nerve. In ALS, it showed evidence of increased persistent sodium‐conductance and reduced potassium‐conductance, both of which may contribute to axonal hyperexcitability and fasciculation . Furthermore, the presence of increased persistent sodium‐conductance was shown to be correlated with more rapid functional decline and shorter survival, and the presence of fasciculation with shorter survival .…”
mentioning
confidence: 99%
“…; Park et al . ). Using axonal excitability, an early study found evidence for a reduction in K + conductances in patients with ALS, and this was reproduced in the rat in vitro using the K + channel blockers tetraethylammonium and 4‐aminopyridine (Bostock et al .…”
Section: Introductionmentioning
confidence: 97%
“…These studies put a focus on axonal ion channels as a source of abnormality, clinical features and potentially novel therapies (Park et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Intramembrane processes such as ionconductance channels can be studied using a technique developed for use in humans as an extension of the threshold electrotonus technique developed by Hugh Bostock. These methods can specifically evaluate axonal excitability changes owing to alterations in slow and fast conductance channels specific to a variety of ions, and have shown abnormalities in ALS, diabetic neuropathy, and other peripheral nerve processes [11]. Given that abnormal excitability in axons and cell bodies has been suggested to be important in ALS, these techniques are currently being utilized in several clinical trials studying drugs expected to affect ion channels.…”
mentioning
confidence: 99%